SHM_415524_HST_3D Stone Boat Axe type A (Gillhög) - Hagaeus, Thomas; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a stone boat axe type A from the Swedish Middle Neolithic, collected in Skåne and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=846

Link to Sök I Samlingarna

https://samlingar.shm.se/object/A3263973-188D-4C67-9E60-F8D15ECAF039
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Photogrammetry; Dynamic Collections; 3D Model; Museum Object; Swedish Middle Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi